(untitled) (Conference Series, 2022)
Opposing religions can experience prolonged chaos due to conflicts arising from differences in beliefs. Therefore, it is a hope that religious pluralism will provide a fresh outlook on such inter-religious conflicts. Amid these conditions, religious pluralism offers a new approach to reducing and eliminating inter-religious conflicts. Religious pluralism brings in a solution that carries the concept that no religion is superior to the other. It eliminates the differences between each religion and unifies the similarities. However, it actually brings new problems. On the contrary, religious pluralism poses a threat to religions rather than providing relief. The understanding and practice of religious pluralism itself inform them that they bring a new threat to religious harmony and freedom. The purpose of this paper is to reveal the dark side of the notion of religious pluralism. This research is educational in nature to understand the effects of religious pluralism and for those who see religious pluralism as a peacemaker.